Wolbachia and host germline components compete for kinesin-mediated transport to the posterior pole of the Drosophila oocyte. - Russell, S.L.; Lemseffer, N.; Sullivan, W.T. (PLoS Pathogens, 2018)
Widespread success of the intracellular bacterium Wolbachia across insects and nematodes is due to efficient vertical transmission and reproductive manipulations. Many strains, including wMel from Drosophila melanogaster, exhibit a specific concentration to the germplasm at the posterior pole of the mature oocyte, thereby ensuring high fidelity of parent-offspring transmission. Transport of Wolbachia to the pole relies on microtubules and the plus-end directed motor kinesin heavy chain (KHC). However, the mechanisms mediating Wolbachia's association with KHC remain unknown. Here we show that reduced levels of the host canonical linker protein KLC results in dramatically increased levels of Wolbachia at the oocyte's posterior, suggesting that KLC and some key associated host cargos outcompete Wolbachia for association with a limited amount of KHC motor proteins. Consistent with this interpretation, over-expression of KHC causes similarly increased levels of posteriorly localized Wolbachia. However, excess KHC has no effect on levels of Vasa, a germplasm component that also requires KHC for posterior localization. Thus, Wolbachia transport is uniquely KHC-limited because these bacteria are likely outcompeted for binding to KHC by some host cargo/linker complexes. These results reveal a novel host-symbiont interaction that underscores the precise regulation required for an intracellular bacterium to co-opt, but not disrupt, vital host processes.